TRADITIONS OF FABRIC AND METAL WORKING IN VALLEY CRAFTS - Usmanov Akhrorjon Rustamjon ugli (Sciental Journals Publishing, 2025)
This article covers the intangible cultural heritage of the Fergana Valley, types of folk crafts and the knowledge, skills and qualifications associated with them, as well as information about crafts. The history of the development of crafts in the valley and their widespread spread among the people is covered extensively and in detail.
Keywords: Pottery, carpentry, blacksmithing, coppersmithing, construction, sewing, weaving, jewelry, embroidery, goldsmithing, painting,